Los efectos de la red social Facebook en el comportamiento electoral de los estudiantes de segundo año de bachillerato del Colegio “Beatriz Cueva de Ayora” y en los alumnos de último año de la carrera de Comunicación Social de la Universidad Nacional de Loja - Torres Salazar, Jhony Patricio (2020)
Since the emergence of social networks on web 2.0, interest has been unleashed for analyzing the consequences of using the social network Facebook; Therefore, the present research, sought to know what effects and what is the influence that said network social, it has about the electoral behavior in the students of the second year of High School Beatriz Cueva de Ayora and those of the last year of the Social Communication of the National University of Loja. In the development of the research was considered important to know how young people accept the issues politicians published on the social network Facebook, during the electoral contests sectionals 2019. It was essential to use two research methods: qualitative and quantitative, through them, for the collection of information, it was also used, three techniques or tools such as the application of surveys, interviews and files observation. The surveys were applied to a significant sample of the two groups in study, being the key to the continuity of the research work. With the use From this methodology, it was evidenced that there is a lack of culture on Facebook critical-propositive policy, due to the overabundance of sarcastic publications Against the candidates. Thus one of the main objectives was fulfilled, which consisted of externalize, what is the influence that social network has on the student population, in as for political issues, especially in electoral seasons. Based on these results a proposal was developed, which consists of creating a Facebook fanpage, to contribute to youth training, regarding political and electoral processes.